2021
DOI: 10.1111/his.14565
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous adenoid cystic carcinoma: a clinicopathologic, immunohistochemical, and fluorescence in‐situ hybridisation study of 13 cases

Abstract: Aims This study aimed to investigate the clinical, histological, immunohistochemical and chromosomal features of primary cutaneous adenoid cystic carcinoma (PCACC). Methods and results We retrospectively analysed 13 cases identified on their clinicopathological features and performed fluorescence in‐situ hybridisation (FISH) on six available cases. Head and neck (46.2%) were most commonly involved. The median age was 53 years, with a male predilection. Histologically, tumours were classified as grades 1 (eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The myoepithelial cell layer is positive for p63, smooth muscle actin, and S100 around the periphery of the cellular aggregates 31 . Approximately 60% of PCACCs harbor MYB gene activations, either through MYB chromosomal abnormalities or MYB proto-oncogene, transcription factor/nuclear factor I/B ( MYB::NFIB ) fusion 32,33 . Histomorphologically, PACC is indistinguishable from ACC of other anatomic sites, and in some cases, metastasis should be excluded clinically.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The myoepithelial cell layer is positive for p63, smooth muscle actin, and S100 around the periphery of the cellular aggregates 31 . Approximately 60% of PCACCs harbor MYB gene activations, either through MYB chromosomal abnormalities or MYB proto-oncogene, transcription factor/nuclear factor I/B ( MYB::NFIB ) fusion 32,33 . Histomorphologically, PACC is indistinguishable from ACC of other anatomic sites, and in some cases, metastasis should be excluded clinically.…”
Section: Discussionmentioning
confidence: 99%
“…One of our cases, the MYB BA test was positive; however, the sample was nonanalyzable for presence MYB-NFIB fusion. Approximately 70% of ACC (including cases of PCACC) can harbor MYB gene activations, either through MYB chromosomal abnormalities or by the generation of the MYB::NFIB fusion 33,35–38 . Expression of MYB protein in ACC appears to lack a strong correlation with the translocation of the MYB gene, and some studies have demonstrated that immunohistochemical expression of MYB can be seen in ACC without rearrangement of the MYB gene and absence of expression has been observed in cases of ACC showing the rearrangement 36 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular biology: Fusions of MYB or MYBL1 with NFIB are detected in 40-97% of adenoid cystic carcinomas with very high specificity [5,6,12,16,19,20]. The most frequent fusions are MYB::NFIB fusion (73-83%) and MYBL1::NFIB (20-23%) [16,[21][22][23][24], with detection of gene rearrangement in both myoepithelial and ductal epithelial cells [22]. Up to 83% of cutaneous cases demonstrate MYB rearrangement.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 99%